Pengembangan Sistem Pendataan Warga Berbasis Aplikasi Digital untuk Meningkatkan Efektivitas Adminitrasi Desa - Ginting, Payung; Gea, Baharui; Sunarya, Irwan; Muslimin, Muslimin; Suhaeri, Suhaeri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The advancement of information technology in the era of Industry 4.0 requires public services to adapt at all levels, including the Village and Community. Perumahan Metro Munjul, a densely populated area with high social and economic activity, faces challenges in population administration that are still carried out manually using registration books. This results in non-integrated data, slow service, risk of data duplication, and lack of transparency. This community service activity, conducted through Kuliah Kerja Nyata (KKN), aims to improve the effectiveness of village administration by implementing a digital-based resident data system. The implementation method uses a participatory and applied approach, including stages of preparation, development of a smartphone-based application (web/mobile), migration of manual data to digital format, training for village officials, and the creation of Standard Operating Procedures (SOP). The results of this activity show that the implementation of a digital application can speed up the process of recording and providing administrative services, securely integrate resident data in the cloud, and improve public transparency. Program evaluation indicates an increase in the competence of village officials in managing digital data, making administrative services in Perumahan Metro Munjul more effective, accurate, and responsive to residents' needs.